The combat between the world and the earth: An interpretive «fight» - Belgrano, Mateo (Pensamiento. Revista de Investigación e Información Filosófica, 2021)
Heidegger characterizes the work of art in his text: «The Origin of the Work of Art» as the combat between the world and the earth in his conference «The Origin of the work of arte». What does this pair of concepts mean? In this work we will try to answer this question by tracing the roots of these concepts in, fundamentally Being and Time, but also some seminars that surround the work of 1927 and the conference discussed. Our thesis is that the concept of «world» is maintained in a certain way, in its connection with significance, as that semantic space from which entities can manifest. But what changes with respect to this concept in «The Origin of the Work of Art» is the instance that institutes it: it is no longer Dasein who opens the world with its action but the work of art. We argue, on the other hand, that the earth has a double meaning: first, it is what allows matter to occur as a phenomenon as such (as opposed to Being and time that always occurred on a pragmatic horizon) and, second, it is the reserve instance of meaning.
Keywords: world; earth; significance; truth